Taxonomic placement of Tanaecium mutabile (Bignonieae, Bignoniaceae) based on new morphological data and phylogenetic analyses - Frazão, Annelise; Lohmann, Lúcia G. (Phytotaxa, 2020)
During ongoing taxonomic studies with Tanaecium, we identified some morphological disparities between Tanaecium mutabile and the remaining species of the genus. Here, we reconstruct a molecular phylogeny of Tanaecium based on two molecular markers (i.e., the chloroplast ndhF and the nuclear pepC), and a broad sampling of members of the Arrabidaea and allies clade, where Tanaecium is included. In the newly constructed phylogeny, T. mutabile is nested within Fridericia, indicating the need for taxonomic arrangements. These findings are further supported by new morphological data (e.g., venation angle, domatia type, and corolla curvature). Based on these results, we formally transfer T. mutabile into Fridericia, and propose the necessary new combination. We further designate a new lectotype for Arrabidaea muehlbergiana, a synonym of T. mutabile. Morphological comparisons between T. mutabile and other morphologically similar species are presented.